2019
DOI: 10.1177/1093526619865641
|View full text |Cite
|
Sign up to set email alerts
|

Parvovirus B19 Myocarditis: Looking Beyond the Heart

Abstract: Human parvovirus B19 represents the most common etiology of myocarditis in the pediatric population. Although it usually causes a benign exanthematic viral infection, parvovirus B19 may also present as disseminated disease with tropism for the myocardium, causing heart failure with high mortality. We present the case of a 2-year-old patient with fulminating acute myocarditis in whom the histological, immunophenotypic, and microbiological findings in necropsy showed multiorgan involvement caused by parvovirus B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…Contrary to other viruses, B19V infects coronary endothelium rather than cardiac muscle cells. The course of B19V myocarditis is different from myocarditis caused by other viruses, as the damaged endothelial cells cause myocardial ischemia and cardiac dysfunction [22][23][24].…”
Section: Rare Manifestations Of Parvovirus B19 Infectionmentioning
confidence: 99%
“…Contrary to other viruses, B19V infects coronary endothelium rather than cardiac muscle cells. The course of B19V myocarditis is different from myocarditis caused by other viruses, as the damaged endothelial cells cause myocardial ischemia and cardiac dysfunction [22][23][24].…”
Section: Rare Manifestations Of Parvovirus B19 Infectionmentioning
confidence: 99%
“…This is a literature review of 32 reported pediatric cases of B19V-associated myocarditis [ 29 - 53 ]. We found that immunosuppressive drugs and immunoglobulin administration may lead to good outcomes in pediatric patients (p-value 0.006 and 0.004, respectively) but this could be related to a limited number of cases.…”
Section: Reviewmentioning
confidence: 99%
“…Pri otrocih opisujejo tudi primere miokarditisa. Parvovirus B19 se rad veže na celice srËne mišice in povzroËi imunsko posredovane okvare miokarda s hipoksiËno-ishe-miËnimi okvarami (10). V primerjavi s šesto otroško boleznijo, ki je znaËilna za dojenËke in majhne otroke, se peta otroška bolezen pojavlja pretežno pri šolskih otrocih.…”
Section: Prikaz Primeraunclassified